Comprehensive Treatment of Severe Periodontal and Periimplant Bone Destruction Caused by Iatrogenic Factors - Gregor-Georg Zafiropoulos; Andreas Parashis; Taha Abdullah; Evangelos Sotiropoulos; Gordon John (Case Reports in Dentistry)
Dental implant success requires placement after periodontal therapy, with adequate bone volume, plaque control, primary stability, control of risk factors, and use of well-designed prostheses. This report describes the surgical and prosthetic management of a patient with severe iatrogenic periodontal/periimplant bone destruction. Methods. A 55-year-old female smoker with fixed partial dentures (FPDs) supported on teeth and implants presented with oral pain, swelling, bleeding, and a 10-year history of multiple implant placements and implants/prosthesis failures/replacements. Radiographs showed severe bone loss, subgingival caries, and periapical lesions. All implants and teeth were removed except implants #4 and #10 which served to retain an interim maxillary restoration. Bone defects were covered with nonresorbable dPTFE membranes. In the mandible, three new implants were placed and loaded immediately with a bar-retained temporary denture. Results. Seven months postoperatively, the bone defects were regenerated, and three additional mandibular implants were placed. All mandibular implants were splinted and loaded with a removable overdenture. Conclusions. In this case, periimplant infection and tissue destruction resulted from the lack of periodontal treatment/maintenance and failure to use evidence-based surgical and loading protocols. Combination therapy resolved the disease and the patient's severe discomfort while providing immediate function and an aesthetic solution.